Surgery for Diffuse WHO Grade II Gliomas: Volumetric Analysis of a Multicenter Retrospective Cohort From the German Study Group for Intraoperative Magnetic Resonance Imaging. Issue 1 (1st October 2019) - Scherer, Moritz; Ahmeti, Hajrulla; Roder, Constantin; Gessler, Florian; Jungk, Christine; Pala, Andrej; Mayer, Benjamin; Senft, Christian; Tatagiba, Marcos; Synowitz, Michael; Wirtz, Christian Rainer; Unterberg, Andreas W; et al.
Abstract: BACKGROUND: In diffuse WHO grade II gliomas (LGG), the extent of resection (EOR) required to achieve significant survival benefits remains elusive. OBJECTIVE: To evaluate the association of residual volume (RV) and EOR with progression-free survival (PFS) or overall survival (OS) in LGG in a retrospective, multicenter series by the German study group of intraoperative MRI (GeSGIM). METHODS: Consecutive cases were retrospectively assessed from 5 centers. Tumors were volumetrically quantified before and after surgery, and clinical data were analyzed, including IDH mutations and neurologic deficits. Kaplan–Meier estimates, accelerated failure time models (AFT), and multivariate Cox regression models were calculated to identify determinants of survival. RESULTS: A total of 140 cases were analyzed. Gross total resection (GTR) was associated with significantly longer PFS compared to any incomplete resection ( P  = .009). A significant survival disadvantage was evident even for small (>0-5 ml) residuals and increased for moderate (>5-20 ml) and large remnants (>20 ml) P  = .001). Accordingly, PFS increased continuously for 20% incremental steps of EOR ( P  < .001). AFT models supported the notion of a continuous association of RV and EOR with PFS. Multivariate Cox regression models confirmed RV ( P  = .01) and EOR ( P  = .005) as continuous prognosticators of PFS. Univariate analysis showed significant associations of RV and EOR with OS. CONCLUSION: Our data support the hypothesis of a continuous relationship of RV and EOR with survival for LGG with superiority seen for GTR. Hence, GTR should be achieved whenever safely feasible, and resections should be maximized whenever tumor has to be left behind to spare function.